(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Tomato fruits are one of the most commonly consumed vegetables worldwide for their health as well as nutritional benefits. However, the fruits contain a lot of water which predisposes them to spoilage by microorganisms that makes its storage and transportation difficult. In the present study, the work was carried out to determine the proximate and minerals composition of three tomato fruits cultivars namely: DanEka, Bahaushe and UTC grown in Sokoto, Sokoto State, Nigeria. Tomato samples were collected from different sales outlets (Kasuwar DanKure and Kasuwar Daji) in Sokoto metropolis and were analyzed for proximate and mineral contents using standard laboratory procedures. Results showed that UTC had highest proteins (1.68%), carbohydrates (91.52%), magnesium (3.6 ppm), sodium (14.0 ppm) and potassium (0.994 ppm) contents but was the least in moisture (90.2%), crude fat (0.2%) and calcium (1.5 ppm). On the other hand, DanEka was observed to have least protein (0.70%), carbohydrates (89.08%), ash (0.02%), magnesium (2.7 ppm) and phosphorus (0.795 ppm) but had the highest moisture (95.2%) and calcium (1.6 ppm) contents. Conversely, the highest crude fat (4.0%) and least sodium (8 ppm) contents were recorded in Bahaushe. It was however moderate in moisture, carbohydrates, protein, magnesium and phosphorous. The proximate compositions have shown that the cultivars were of high nutritional quality and UTC could stand longer postharvest storage period considering its lower moisture content